Effects of performance goals and social norms on academic dishonesty in a test. (30th July 2019) - Daumiller, Martin; Janke, Stefan
Abstract : Background: Previous research has shown that achievement goals affect the frequency of academic dishonesty. However, mixed findings suggest that especially the effect of performance goals might depend on contextual factors. Aims: We wanted to investigate whether crucial aspects of the achievement situation influence the magnitude of the effect of performance goals (here: focused on appearance) on dishonesty. Specifically, we propose that social norms regarding the acceptance of dishonesty moderate the positive effect of performance goals on academic dishonesty. Sample: We sampled 105 German university students. They were teacher trainees, mostly in their first year at university and on average 20.6 ( SD  = 3.6) years old (72.4% female). Method: We conducted a 2 (induced appearance goals vs. no goal induction) × 2 (cheating confederate vs. no observable cheating behaviour by this person) experiment. A manipulation check confirmed that the manipulation of appearance goals was successful. Cheating behaviour was observed by a confederate student and subsequently classified by two raters. Additionally, participants' dishonesty in self‐presentation questions was measured using deviations from baseline measures. Results: The induction of appearance goals only led to increased cheating when the social norm suggested that cheating behaviour was an acceptable way to increase performance (i.e., cheating confederate condition). For deceiving, we found a positive main effect of appearance goals. Appearance goals mediated these effects from goal manipulation on academic dishonesty. Conclusions: Taken together, our results highlight that the mixed findings on the effect of performance goals on academic dishonesty might be due to uninvestigated moderators such as social norms. Future research should build on these findings to identify additional moderators.